Clinical study on acupuncture treatment of hypertension with hyperactivity of liver yang. Issue 17 (30th April 2021) - Wu, Jiaojuan; Zhang, Xudong; Zhao, Jiping; Xue, Yanjun; Yu, Pengcheng; Wu, Xiaoli; Liu, Qingguo
Abstract: Introduction: Hypertension can lead to different degrees complications of cardiovascular and cerebrovascular, and increase the risk of sudden death. Acupuncture has become a complementary alternative therapy for hypertension because of its antihypertensive and nontoxic side effects. However, there is still lack of evidence-based medicine evidence for an effective acupuncture antihypertensive prescription. The purpose of this study is to evaluate the effect of a special acupuncture prescription on hypertension with hyperactivity of liver yang. Methods: In this randomized controlled trial, we will recruit 56 hypertensive patients with hyperactivity of liver yang. Then the patients will be randomly divided into control group and experimental group. The control group will be treated with western medicine, and the experimental group will be treated with medicine combined with acupuncture. The intervention will last 4 weeks. The indices will be collected before acupuncture, after acupuncture, and 2 weeks after acupuncture. The primary outcome will be 24-hour ambulatory blood pressure. The secondary outcomes will be clinic blood pressure, anxiety and depression score, and the syndrome score of hyperactivity of liver yang. The auxiliary indicators will be blood pressure load values and salt sensitivity risk rate. The exploratory indicator will be acupoint diagnosis. The safety evaluation indicator will be incidence of adverse events. Discussion: The results of this study will provide favorable evidence for the efficacy and safety of acupuncture in reducing blood pressure, and explore the positive reaction acupoints which related to hypertension.